Secondary structure polymorphism in Oxytricha nova telomeric DNA - Krafft, Christoph (Oxford University Press, 2002)
Tandem repeats of the telomeric DNA sequence d(T(4)G(4)) of Oxytricha nova are capable of forming unusually stable secondary structures incorporating Hoogsteen hydrogen bonding interactions. The biological significance of such DNA structures is supported by evidence of specific recognition of telomere end-binding proteins in the crystal state. To further characterize structural polymorphism of Oxytricha telomeric DNAs, we have obtained and interpreted Raman, ultraviolet resonance Raman (UVRR) and circular dichroism (CD) spectra of the tandem repeats d(G(4)T(4)G(4)) (Oxy1.5), d(T(4)G(4))(2) (Oxy2) and dT(6)(T(4)G(4))(2) (T6Oxy2) and related non-telomeric isomers in aqueous salt solutions. Raman markers of Oxy1.5 identify both C2′-endo/anti and C2′-endo/syn conformations of the deoxyguanosine residues and Hoogsteen hydrogen bonded guanine quartets, consistent with the quadruplex fold determined previously by solution NMR spectroscopy. Raman, UVRR and CD signatures and Raman dynamic measurements, to monitor imino NH→ND exchanges, show that the Oxy1.5 antiparallel quadruplex fold is distinct from the hairpin structures of Oxy2 and T6Oxy2, single-stranded structures of d(TG)(8) and dT(6)(TG)(8) and previously reported quadruplex structures of d(T(4)G(4))(4) (Oxy4) and dG(12). Spectral markers of the telomeric and telomere-related DNA structures are tabulated and novel Raman and UVRR indicators of thymidine and deoxyguanosine conformations are identified. The results will be useful for probing structures of Oxytricha telomeric repeats in complexes with telomere end-binding proteins.